Reformasi Birokrasi dalam Pemikiran Muhammad Abduh: Respons terhadap Realitas Politik Dunia Islam - Ahmad Faris (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Scholarship on Muhammad Abduh commonly treats theological, educational, and political reform as separate domains. Consequently, the administrative dimension of his thought—how public authority should be constrained, organized, supervised, and oriented toward public welfare—remains insufficiently developed. This article reconstructs a conception of bureaucratic reform from Abduh's thought as a response to colonialism, authoritarian rule, elite domination, and institutional stagnation in nineteenth-century Egypt. It employs a qualitative-historical design combining conceptual analysis and contextual hermeneutics of Abduh's primary writings, al-Urwah al-Wuthqa, and scholarship on Islamic reform and public administration. The findings show that, although Abduh did not employ the contemporary term bureaucratic reform, his work contains an ethical-institutional architecture comprising six principles: law-bound civil authority, constitutional constraint, consultation and public accountability, differentiated yet coordinated state functions, administrative decentralization, professionalization through education and ijtihad, and legal adaptation to social change. The article proposes an Abduhian model of bureaucratic reform that links epistemic reform to institutional capacity and justice-oriented public service. Its theoretical contribution lies in connecting modern Islamic political thought with the literature on quality of government, while demonstrating that reform in Muslim-majority settings requires an integrated transformation of rules, competence, and administrative ethics.